CD4 T cell memory derived from young naive cells functions well into old age, but memory generated from aged naive cells functions poorly - Haynes, Laura (National Academy of Sciences, 2003)
Age-related declines in immune function have an impact on both primary and memory responses. In this study, we have examined the ability of naive CD4 T cells from young and aged T cell receptor transgenic mice to establish functional memory. We found that memory cells generated from young CD4 T cells responded well to antigen, even a year after generation, whereas memory cells derived from CD4 T cells from aged mice responded poorly both ex vivo and in vivo. Memory cells generated from aged naive cells proliferate less, produce reduced levels of cytokines, and exhibit reduced cognate helper function, compared with memory cells generated by using young naive cells. These results indicate that it is the age of the naive T cell when it first encounters antigen, rather than the age when it reencounters antigen, that is critical for good memory CD4 T cell function.